Brief assessment of depression: Psychometric properties of the Portuguese version of the Patient Health Questionnaire (PHQ-9) - Ferreira, Tiago (2019)
: The lack of knowledge regarding psychometric characteristics of brief scales for assessing the severity of symptoms of depression for the Portuguese population limits the ability of health professionals to signal clinically relevant situations, as well as the implementation of alternative forms of mental health care. The Patient Health Questionnaire (PHQ-9) is a scale whose usefulness in various professional contexts has been amply demonstrated by research. However, some of its psychometric qualities remain unknown for the Portuguese version.